Agents of dissent: African student organizations in the German Democratic Republic. (16th January 2019) - Pugach, Sara
Abstract: African students in the German Democratic Republic (GDR) often belonged to national student clubs (NHG) that were arranged for them by the East German government. Many were also members of an umbrella organization for all African students and workers in the GDR (UASA). While the GDR authorities thought that the NHG and UASA would adopt political positions that reflected those of the GDR, this article demonstrates that the students instead used them to criticize both their own governments and their host country. It shows that the students often held positions contrary to the GDR's, and were not shy about expressing them. Although they were usually unable to organize as openly as students in the West, African students in the GDR held meetings and wrote letters to protest about a variety of issues, including Sékou Touré's repression of a teachers' strike in Guinea, the Biafran crisis in Nigeria and ethnic separatism in Kenya. They also took the GDR to task for the racist behaviour of East German citizens. The GDR's Socialist Unity Party claimed that the country was anti-racist and anti-imperialist, and that all vestiges of Nazism had been expunged; the students, however, were able to point out multiple racist incidents, and through the UASA demanded that the GDR address its racism problem. Résumé: En République démocratique allemande (RDA), les étudiants africains étaient souvent membres de clubs étudiants nationaux (NHG) mis à leur disposition par le gouvernement est-allemand. Beaucoup étaient également affiliés à une organisation parapluie regroupant les étudiants et travailleurs africains en RDA (UASA). Alors que les autorités est-allemandes pensaient que les NHG et l'UASA adopteraient des positions politiques qui reflèteraient celles de la RDA, cet article démontre que les étudiants ont au contraire utilisé ces groupes pour critiquer leurs propres gouvernements et leur pays d'accueil. Il montre que les étudiants avaient souvent des positions contraires à celles de la RDA et ne craignaient pas de les exprimer. Ils ne pouvaient pas s'organiser aussi ouvertement que les étudiants de RFA, mais les étudiants africains en RDA tenaient des réunions et écrivaient des lettres de protestation sur différents sujets comme la répression d'une grève d'enseignants par Sékou Touré en Guinée, la crise du Biafra au Nigeria ou le séparatisme ethnique au Kenya. Ils ont également pris la RDA à partie pour le comportement raciste des citoyens est-allemands. Le Parti socialiste unifié de la RDA affirmait que le pays était antiraciste et anti-impérialiste, et que tous les vestiges du nazisme avaient été effacés ; les étudiants ont cependant pu relever de multiples incidents racistes et, par le biais de l'UASA, exiger que la RDA s'attaque à son problème de racisme.